Description of two new taxa of Hemileucinae from southern Peru: Molippa kohlli Racheli, sp. n. and Paradirphia wenczeli Racheli, sp. n. (Lepidoptera: Saturniidae) - L. Racheli (SHILAP)
Se describen y figuran dos nuevas especies de Hemileucinae de Perú: Molippa kohlli Racheli, sp. n. y Paradirphia wenczeli Racheli, sp. n.